A novel trivalent non-Fc anti-CD3 Collabody preferentially induces Th1 cell apoptosis in vitro and long-lasting remission in recent-onset diabetic NOD mice - Huang, Chuan-Chuan; Sung, Hsiang-Hsuan; Li, Hsiu-Chuan; Miaw, Shi-Chuen; Kung, John T.; Chou, Min-Yuan; Wu-Hsieh, Betty A. (Frontiers in Immunology, 2023)
Specific anti-CD3 treatment is deemed to be a promising therapy for allograft rejection and type 1 diabetes (T1D). Fc receptor (FcR) reduced-binding antibodies by avoiding adverse effects of Fc and FcR interaction have good therapeutic potential. We generated a trivalent anti-mouse-CD3 Collabody, h145CSA, by using a triplex-forming collage-like peptide (Gly-Pro-Pro) 10 to drive the trimerization of the Fab fragments. Exposure to h145CSA, but not its bivalent counterparts 145-2C11 and h145chIgGAA (FcR reduced-binding format), upregulates FasL expression on Th1 cells and causes Th1 cell apoptosis. Administration of h145CSA invokes minimal mitogenic effects in mice. The ability of multiple dosing of h145CSA to induce splenic CD4 + T cell depletion is comparable to bivalent antibodies but is characterized by more rapid CD4 + T cell recovery kinetics.h145CSA is more potent than h145chIgGAA in inducing long-lasting remission in recent-onset diabetic NOD mice. Its therapeutic effect is accompanied by significantly lower percentage of CD4 + IFNg + T cells and higher Treg/Th1 ratio in pancreatic and mesenteric lymph nodes. The results of our study demonstrate that trivalent non-Fc anti-CD3 Collabody has potential to be used in treatment of T1D.